Impact of flavour solvent on biscuit micro-structure as measured by X-ray micro-computed tomography and the distribution of vanillin and HMF (HPLC) - Yang, Ni; Fisk, Ian D.; Linforth, Rob S.T.; Brown, Keith; Walsh, Stuart; Mooney, Sacha J.; Sturrock, Craig; Hort, Joanne (Springer Verlag (Germany), 2012)
The influence of flavour solvent, propylene glycol (PG) and triacetin (TA), was investigated on the micro-structure (as measured by X-ray micro-Computed Tomography, X-ray μCT) and aroma compound distribution (as measured by HPLC) within shortcake biscuits. X-ray μCT scanning showed biscuits made with PG had smaller pores and higher porosity than biscuits made with TA. Vanillin distribution across the biscuits was not homogeneous and was found at higher concentrations in the centre of the biscuits than the edge or bottom. The baked aroma compound 5-hydroxymethyl-furfural (HMF) was present at higher concentrations at the surface of the biscuits where Maillard chemistry is presumed to occur at its highest rate. The type of solvent had a significant effect on the total concentration and distribution of aroma compounds (p < 0.05). TA biscuits retained greater vanillin and more HMF was formed during baking when compared to PG biscuits. The core of TA biscuits had (on a relative scale) a much greater vanillin and lower HMF concentration than PG biscuits when compared to their periphery. Although this may be due to different physicochemical properties of the two solvents and varying levels of interactions with other ingredients, the micro-structure differences indicated by X-ray μCT image analysis illustrate one potential route by which the flavour solvent may be influencing the generation and stability of biscuit aroma compounds.